A new risk reduction indicator for dam safety management combining efficiency and equity principles. Issue 9 (2nd September 2017) - Serrano-Lombillo, Armando; Morales-Torres, Adrián; Escuder-Bueno, Ignacio; Altarejos-García, Luis
Abstract: Large dams are critical infrastructures whose failure could produce high economic and social consequences. Risk analysis has been shown to be a suitable methodology to assess these risks and to inform dam safety management. In this sense, risk reduction indicators are a useful tool to manage risk results, yielding potential prioritisation sequences of investments in dams' portfolios. Risk management is usually informed by two basic principles: efficiency and equity. These two principles many times conflict, requiring a trade-off between optimising the expenditures and providing a high level of protection to all individuals. In this paper, the risk reduction indicator Equity Weighted Adjusted Cost per Statistical Life Saved (EWACSLS) is presented. This indicator allows obtaining prioritisation sequences of investments while maintaining an equilibrium between equity and efficiency principles. In order to demonstrate its usefulness, it has been applied in a real-world case study, a portfolio of 27 dams where 93 structural and non-structural investments are prioritised. The EWACSLS indicator is analysed in detail and its results are compared with other existing risk reduction indicators, showing its flexibility and how it can be a very well balanced indicator for the purpose of prioritisation of risk reduction measures.